2018
DOI: 10.1016/j.matpr.2018.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Subgrains, micro-twins and dislocations characterization in monolike Si using TEM and in-situ TEM

Abstract: A critical aspect in the development of mono-like Silicon for photovoltaic (PV) application lies in the control of its defect microstructure. While micro-twins do not seem to represent a major concern regarding electrical activity, some dislocations and low angle grain boundaries need to be avoided in the growing process because of their recombination properties. Here, we have studied how these defects grow and interact together in order to understand what are the mechanisms responsible for their presence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Since the rotation axis is principally along the growth direction, many dislocations have an edge character. This is consistent with the analysis of Lantreibecq et al [18] who found that the SGBs in the source cast mono ingot are mainly composed of dislocations with a [001] line character and a Burgers vector a/2 [11 � 0]. They proposed that these dislocations grow by epitaxy on the solid-liquid interface.…”
Section: Orientation Relationship Of the Subgrainssupporting
confidence: 91%
See 3 more Smart Citations
“…Since the rotation axis is principally along the growth direction, many dislocations have an edge character. This is consistent with the analysis of Lantreibecq et al [18] who found that the SGBs in the source cast mono ingot are mainly composed of dislocations with a [001] line character and a Burgers vector a/2 [11 � 0]. They proposed that these dislocations grow by epitaxy on the solid-liquid interface.…”
Section: Orientation Relationship Of the Subgrainssupporting
confidence: 91%
“…Using b = 0.384 nm for the Burgers' vector magnitude in silicon along a <110> direction, the distance between each dislocation is d1 = 7.3 nm and d2 = 22 nm for θ of 3° and 1°, respectively. These misorientation angles are in the same order of magnitude as what was observed by Lantreibecq et al in the source cast mono ingot at a height of about 160 mm from the melt-back surface [18], which is above the area where electrically active subgrains do appear on the PL maps (cf. Fig.…”
Section: Sgb Misorientations and Their Dislocation Densitysupporting
confidence: 84%
See 2 more Smart Citations
“…Indeed, if the displacement vector is perpendicular to the diffraction vector, the defect is not visible on the topograph. This is the case of dislocations whose image is extinct for the diffraction spots corresponding to diffraction vectors perpendicular to the Burgers vectors as also seen in TEM investigations [68,69]. On the one hand, this means that the absence of a dislocation strain field on a single diffraction spot does not mean that no dislocations are present.…”
Section: Orientation Contrastmentioning
confidence: 85%